The Implementation of Sort-Set in Order-Shine-Standardize-Sustain (5S) for Vocational High School Learners - Mulyani, Tri; Haryadi, Bambang; Qudus, Nur (Journal of Vocational and Career Education, 2023)
Industry demands Vocational High Schools (SMK) graduates to adopt an industrial work culture in Japan, specifically the 5S Principle. Most schools implemented the 5S principle, but its success remains unknown. This research attempted to reveal the planning of the 5S principle in school, learner knowledge, learner attitude, learner behavior, the association of knowledge and attitude to the behavior of 5S learners, and the implementation of the 5S principle. The research method involved conducting case studies at SMK Negeri 2 Salatiga and SMK Negeri Jateng Semarang and analyzing the data using quantitative and qualitative methods. Data collection techniques include initial observations, tests, questionnaires, interviews, and observations for learners during internships in furniture workshops. The results found (1) the 5S principle plan in the form of a special task team, socialization, management planning for the workshop facility and infrastructure, and the supporting program plan; (2) students' knowledge performance shows high results; (3) students' attitudes have obtained good results; (4) students' behavior has obtained high results; (5) there is a relatively perfect relationship between students' 5S knowledge and 5S attitudes towards students' 5S behavior; (6) the implementation of the 5S principle has been successfully implemented in Vocational High Schools (SMK). The research results indicate that the implementation of 5S yielded positive outcomes and can serve as a valuable tool for future enhancements.